Analisis Tarikan Perjalanan Pegawai Kantor Gubernur Sulawesi Tenggara - Syamsuddin Syamsuddin; Sufrianto Sufrianto; Egi Wijaya Kusuma (Sultra Civil Engineering Journal (SCiEJ), 2026)
This study aims to determine: (1) To analyze the factors influencing employee travel in the travel attraction at the Southeast Sulawesi Governor's Office, (2) To obtain and analyze the employee travel attraction model at the Southeast Sulawesi Governor's Office. The population and sample in this study were 80 employees at the Southeast Sulawesi Governor's Office. The data collection techniques used were questionnaires and surveys. Data analysis techniques used validity tests, reliability tests, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests), multiple linear regression tests, correlation analysis, and multiple coefficients of determination. The results of the study indicate that: The variable number of employees (X1) has a coefficient value of 0.657, indicating a dominant influence of (X1) on (Y) of 65.7%. The variable office area (X2) has a coefficient value of 0.663, indicating a dominant influence of (X2) on (Y) of 66.3%. The trip attraction analysis model includes the number of employees (X1), office area (X2), parking area (X3), number of car owners (X4), number of motorcycle owners (X5), distance to destination (X6), and travel time to destination (X7). Therefore, it can be concluded that (X1) and (X2) influence the trip attraction of employees at the Southeast Sulawesi Governor's Office. The resulting model is as follows: Y = 1.264 + 0.657 (X1) + 0.663 (X2).